Higher Concentration of Taenia Antigens in the CSF is Related to Slight Ventricle Enlargement and Periventricular Neuronal Decrease in Young Rats - Silva, Monica Almeida [UNESP]; Barcelos, Eduardo Vieira [UNESP]; Aves Junior, Aderaldo Costa [UNESP]; Generoso, Diego [UNESP]; Alda, Maiara Almeida; Batah, Sabrina Setembre; Fabro, Alexandre Todorovic; Machado, Vania Maria de Vasconcelos [UNESP]; Hamamoto Filho, Pedro Tadao [UNESP]; Zanini, Marco Antonio [UNESP] (Georg Thieme Verlag Kg, 2020)
Purpose Experimental models might help understand the pathophysiology of neurocysticercosis-associated hydrocephalus. The present study aimed to compare the extent of hydrocephalus and tissue damage in rats with subarachnoid inoculation of different concentrations of Taenia crassiceps cyst proteins. Methods Sixty young rats were divided into two groups: low- and high-concentration groups. The animals in the low concentration group received 0.02ml of 2.4mg/ml T. crassiceps cyst proteins while those in the high concentration group received 0.02 ml of 11.6mg/ml T. crassiceps cyst proteins. The animals underwent magnetic resonance imaging at 1, 3, and 6 months postinoculation to assess the ventricle volume. Morphological assessment was performed at the end of the observation period. Results Repeated measures of ventricle volumes at 1, 3, and 6 months showed progressive enlargement of the ventricles. At 1 and 3 months, we observed no differences in ventricle volumes between the 2 groups. However, at 6 months, the ventricles were larger in the high concentration group (median = 3.86mm(3), range: 2.37-12.68) compared with the low concentration group (median = 2.00mm(3), range: 0.37- 11.57), p = 0.003. The morphological assessment revealed a few inflammatory features in both groups. However, the density of oligodendrocytes and neurons within the periventricular region was lower in the high concentration group (5.18 versus 9.72 for oligodendrocytes and 15.69 versus 21.00 for neurons; p < 0.001 for both). Conclusion Our results suggest that, in rats, a higher concentration of T. crassiceps cyst proteins in the subarachnoid space could induce ventricle enlargement and reduce the number of neurons within the periventricular area.
Keywords: neurocysticercosis; hydrocephalus; neurons; experimental model